SUSTAINABLE BRANDING OF FORESTRY ENTERPRISES: BUILDING TRUST AND COMPETITIVE ADVANTAGES - Moran, Oleksandr; Kuzma, Oleksandr (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The report examines theoretical and practical aspects of forming sustainable branding of forest enterprises as a tool for ensuring stakeholder trust and creating long-term competitive advantages. Global trends in consumer behavior in the field of forest products are analyzed based on data from the FSC-IPSOS 2025 global study. The international experience of Stora Enso and IKEA is highlighted, demonstrating both successful sustainable branding strategies and reputational risks in case of non-compliance with declared goals. Special attention is paid to the current state of the Ukrainian forest sector, reform processes, restoration of FSC certification and dynamics of export indicators. Based on the analysis, practical recommendations are proposed for forming effective sustainable branding for Ukrainian forest enterprises.